A Hidden Metastasis with a Bloomy Rind Sign: Carcinomatous Meningitis from Metastatic Lung Adenocarcinoma with Unusual Cranial Nerve Involvement - Tanvi Joshi; Adrian Jacob; Swetha Narla; M Balamurugan (Indian Journal of Neurosurgery)
Carcinomatous meningitis, also known as leptomeningeal metastasis, is a rare and often under-recognized manifestation of advanced cancer. It occurs when malignant cells invade the leptomeningeal layers surrounding the brain and spinal cord, leading to a range of neurological symptoms. It remains a diagnostic challenge due to its nonspecific clinical presentation and the complexity of distinguishing it from other neurological conditions. Our case report highlights a rare and unique presentation of carcinomatous meningitis in a patient with an underlying, previously undiagnosed malignancy. The patient initially presented with left-sided facial pain, decreased sensation over the left side of the face, drooling of saliva, and coughing while eating, which raised suspicion for possible posterior fossa lesion. Magnetic resonance imaging (MRI) of the brain with contrast revealed fusiform thickening of the left trigeminal nerve, which was suggestive of a granulomatous lesion. FLAIR also showed bloomy Rind sign. CSF studies showed atypical malignant cells. A multidisciplinary team was set up and endoscopic transnasal transsphenoidal biopsy was done, which was reported as metastatic adenocarcinoma from a primary lung lesion which was confirmed later by PET CT scan. This case emphasizes the importance of considering leptomeningeal metastasis in patients with unexplained neurological signs and symptoms. Multidisciplinary collaboration, including neurosurgery, oncology, and radiology, is essential for accurate diagnosis, staging, and treatment planning. While the prognosis remains poor, early intervention can potentially improve quality of life and extend survival in selected cases.